2018
DOI: 10.1093/aje/kwy094
|View full text |Cite|
|
Sign up to set email alerts
|

Prospects for Tuberculosis Elimination in the United States: Results of a Transmission Dynamic Model

Abstract: We estimated long-term tuberculosis (TB) trends in the US population and assessed prospects for TB elimination. We used a detailed simulation model allowing for changes in TB transmission, immigration, and other TB risk determinants. Five hypothetical scenarios were evaluated from 2017 to 2100: 1) maintain current TB prevention and treatment activities (base case); 2) provision of latent TB infection testing and treatment for new legal immigrants; 3) increased uptake of latent TB infection screening and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 20 publications
(28 reference statements)
2
59
0
Order By: Relevance
“…CDC also recommends testing for TB in health care workers and others who work in places where there is a high risk of TB transmission, persons who are contacts of a person with infectious TB disease, and immunocompromised persons, who have a higher risk for developing TB disease once infected . According to one model, increased uptake of LTBI screening and treatment among populations at higher risk for TB would result in an incidence of 26 new infections per million by 2050 . Detection of LTBI can be improved by the preferential use of interferon‐γ release assays over the tuberculin skin test, especially in persons with a history of Bacillus Calmette‐Guérin vaccination or who are unlikely to return to have their tuberculin skin test read .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDC also recommends testing for TB in health care workers and others who work in places where there is a high risk of TB transmission, persons who are contacts of a person with infectious TB disease, and immunocompromised persons, who have a higher risk for developing TB disease once infected . According to one model, increased uptake of LTBI screening and treatment among populations at higher risk for TB would result in an incidence of 26 new infections per million by 2050 . Detection of LTBI can be improved by the preferential use of interferon‐γ release assays over the tuberculin skin test, especially in persons with a history of Bacillus Calmette‐Guérin vaccination or who are unlikely to return to have their tuberculin skin test read .…”
Section: Discussionmentioning
confidence: 99%
“…This report summarizes provisional TB surveillance data reported to CDC's National Tuberculosis Surveillance System (NTSS) through 2018. Although the total number of cases and incidence are the lowest ever reported in the United States, a recent model predicted that the U.S. TB elimination goal (annual incidence of <1 case per 1 million persons) will not be attained in the 21st century without greatly increased investment in detection and treatment of latent TB infection (LTBI) . Programs to identify, test, and treat populations at high risk for TB remain important to eliminating TB in the United States.…”
Section: Tuberculosis (Tb) Case Counts and Incidence With Annual Percmentioning
confidence: 99%
“…Multiple modeling studies have consistently suggested the solution to this critical question. TB elimination can be achieved through comprehensive strategies directed toward integrated LTBI management with proper active TB management [5,6]. Programmatic management of LTBI is emerging as a critical component of TB control programs for TB elimination [7].…”
Section: Introductionmentioning
confidence: 99%
“…This approach implies that all pulmonary TB patients are equally infectious, while all extrapulmonary patients are entirely non-infectious, and so does not capture the heterogeneity among pulmonary patients. Other TB models have considered sputum smear status as a factor in stratifying patients' levels of infectiousness, considering both smear-negative and smearpositive pulmonary TB to be infectious, with the relative infectiousness of smear-negative patients compared to smear-positive typically set between 15 and 25% [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. While stratifying pulmonary TB patients based on smear status captures an additional clinical attribute that is important in determining infectiousness, even these models still do not capture the full picture of TB patients' infectiousness variation, since several behavioural and demographic factors other than smear status can affect the level of infectiousness [5].…”
Section: Introductionmentioning
confidence: 99%